Analisis Produktivitas Kerja dan Penjadwalan Perawatan Mesin Lipat Divisi Kasa Premium dengan Metode Preventive Maintenance - Setiawati, Nadila Dwi; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. Kasa Husada Wira Jatim is a manufacturing company engaged in the manufacture of medical devices, the products produced are gauze, medical masks, and also cotton. In the production process the system used is Make To Order, this results in the absence of ready stock stored, many delays in completing orders. This study aims to determine the level of work productivity using the Overall Equipment Effectiveness (OEE) method, and also the maintenance schedule for folding machines. The folding machine of the Premium Kasa Division which is often damaged, in the period from August 2024 to July 2025 there were 31 damages with critical components of the knife and seal. From the results of the Mean Time To Failure calculation for the knife component, the replacement time is once every 26 days, for the seal component once every 19 days. This study is expected to minimize delays in completing orders.